2018
DOI: 10.1155/2018/4023178
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ground Fly Ash on Cement Hydration and Mechanical Property of Mortar

Abstract: In this study, the ground fly ash is made of ordinary grade I fly ash by grinding. Compared with grade I fly ash, the influence of ground fly ash on cement hydration and mechanical property of mortar was investigated. e results show that ground fly ash can improve the hydration of cement at all the ages compared with grade I fly ash, and not only does its pozzolanic reaction start earlier, but the reaction degree is higher and the speed is quicker. Before 3 days, the contribution of ground fly ash to the stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Moreover, their use is growing at a faster rate for the development of sustainable cement-based materials [3,4]. Comprehensive analysis has been conducted on these ashes by a variety of investigators to assess their pozzolanic activity [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, their use is growing at a faster rate for the development of sustainable cement-based materials [3,4]. Comprehensive analysis has been conducted on these ashes by a variety of investigators to assess their pozzolanic activity [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon could be due to the addition of fly ash in the concrete. Previously, researchers showed that the presence of fly ash in concrete delays the hydration process and the concrete has low strength in the early stages, and the concrete improves in strength at a later stage (after 60 days) [32,33]. The variations in compressive strength are shown in Figure 3.…”
Section: Mechanical Properties Evolutionmentioning
confidence: 91%
“…Using the fly ash as a partial replacement for cement also contributes to the increase in durability of cement composites as the fly ash is capable of pozzolanic reaction with calcium hydroxide, which produces additional calciumsilicate hydrates (C-S-H) and calcium-aluminium-silicate hydrates (C-A-S-H). ey additionally cause refinement and reduction of permeability of pore structure of cement matrix as the pozzolanic reaction is slower than hydration of cement as presented in the studies of Moffatt et al [12] and Feng et al [13].…”
Section: Introductionmentioning
confidence: 99%